2017
DOI: 10.1016/j.mad.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated alterations in the levels of cytotoxic lipid molecular species and oxidative stress in the murine thymus are reduced by growth hormone treatment

Abstract: During age-associated thymic involution, thymocytes decrease and lipid-laden cells accumulate. However, if and how aging affects the thymic lipid profile is not well understood, nor is it known if the hormonal milieu modifies this process. Here we demonstrate a correlation between reduced thymocyte numbers and markers of inflammation and oxidative stress with age. Evaluating the lipidomics profile of the whole thymus, between the ages of 4 (young) and 18 months (old), we found increased amounts of triacylglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Increased levels of TNF-α and increased expression of CD204, a scavenger receptor of oxidized LDL, were detected in the thymic parenchyma of older individuals, as compared to younger ones. GH reduced thymic levels of TNF-α and HNE and increased the number of thymocytes, in accordance with several observations that indicated growth hormone as a powerful immunomodulating agent, stimulating thymopoiesis and limiting the number of adipocytes and fat locules in rodent and human thymus [ 74 ]. The levels of MDA and protein carbonyls (PC), as well as of oxidized and reduced glutathione and the activities of several antioxidant enzymes were measured in peripheral blood lymphocytes from 100 individuals, equally subdivided into groups of ages varying from 11–20 to 51–60 years.…”
Section: Immunosenescencesupporting
confidence: 86%
See 1 more Smart Citation
“…Increased levels of TNF-α and increased expression of CD204, a scavenger receptor of oxidized LDL, were detected in the thymic parenchyma of older individuals, as compared to younger ones. GH reduced thymic levels of TNF-α and HNE and increased the number of thymocytes, in accordance with several observations that indicated growth hormone as a powerful immunomodulating agent, stimulating thymopoiesis and limiting the number of adipocytes and fat locules in rodent and human thymus [ 74 ]. The levels of MDA and protein carbonyls (PC), as well as of oxidized and reduced glutathione and the activities of several antioxidant enzymes were measured in peripheral blood lymphocytes from 100 individuals, equally subdivided into groups of ages varying from 11–20 to 51–60 years.…”
Section: Immunosenescencesupporting
confidence: 86%
“…This process, which starts early in life, is almost complete by the age of 40–50 years. Increasing formation of lipid-laden cells with aging has also been observed in lympho-hematopoietic organs, including the thymus [ 74 , 75 ]. Age-related thymic involution appears to reflect the compound effects of increased rates of thymocyte death in the thymus and decreased thymic differentiation and output of T cells.…”
Section: Immunosenescencementioning
confidence: 99%
“…A second possibility is that intrathymic LLMC could actually be thymic mesenchymal stromal cells accumulating lipids in response to the inflammatory environment and increase of oxidized LDL and oxidative stress that occurs in the thymus with age [ 33 ]. In this regard, Kirkland and colleagues have suggested that during the natural process of aging, dyslipidemia occurs and distinct mesenchymal cell types might acquire the profile of mesenchymal-adipocyte like default (MAD) cells [ 34 ], in association with the increase of pro-inflammatory molecules in circulation, also known as inflammaging [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adipogenesis within the thymus and thymic atrophy are promoted by age-associated decreases in expression of ghrelin, an orexigenic and anti-inflammatory peptide, and ghrelin receptor (growth hormone secretagogue receptor) in thymic stromal cells (Dixit et al, 2007; Youm et al, 2009). Mechanistic links between aging, thymic adiposity, and thymic atrophy have been revealed by recent work showing that lipotoxic “danger-associated molecular patterns” (DAMPs), such as ceramide and free cholesterol, increase during aging (de Mello-Coelho et al, 2017; Youm et al, 2012), and can initiate NLRP3 inflammasome signaling and IL-1β production in thymic myeloid cells (Youm et al, 2012). Il1r expression was found mainly in the TEC compartment, and since IL-1β causes thymic dysfunction (Morrissey et al, 1988a; Morrissey et al, 1988b) these studies suggest that lipotoxic DAMPs inhibit thymus function via IL-1β signaling in TEC (Youm et al, 2012).…”
Section: Mechanisms Governing Thymic Atrophymentioning
confidence: 99%